Assessing the influence of fibers on the flexural behavior of reinforced concrete beams with different longitudinal reinforcement ratios - Conforti, Antonio (2021)
The use of fibers in reinforced concrete (RC) beams mainly improves both the bearing capacity and the cracking control. In this way, positive effects on the service life of RC structures can be expected. In this paper, the fiber influence on the flexural behavior of RC beams with different longitudinal reinforcement ratios (0.5% ≤ ρs ≤ 1.2%) is analyzed by testing small-scale RC beams. Concretes incorporating 0, 25 and 50 kg/m3 of steel, 6 and 12 kg/m3 of glass macrofibers, and 5 and 10 kg/m3 of polymer macrofibers were studied. Crack and deflection control, as well as bearing capacity and crack localization were evaluated for a broad range of fiber-reinforced concrete (FRC) toughness. It is verified that fibers, in the longitudinal reinforcement ratio considered, improve the bending behavior at serviceability limit state (SLS) and ultimate limit state (ULS) of RC beams, without limiting the structure ductility. It was also confirmed the philosophy of the fib Model Code 2010, such that FRC can be considered as a composite material where performance parameters govern its mechanical behavior. Finally, the several data available allowed to deeply analyze fib Model Code 2010 formulations (mean crack spacing and flexural bearing capacity) and to propose modifications where needed.